IMPROVING THE METHODOLOGY FOR DETERMINING BIOCOMPATIBILITY OF METAL ALLOYS FOR THE PREVENTION OF INTOLERANCE AND GALVANOSIS IN PEOPLE LIVING IN ENVIRONMENTALLY UNFAVORABLE CONDITIONS IN UZBEKISTAN - S.A., , Gafforov (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted tothe improvementof methods for determining the biocompatibility of metal alloys obtained fromvarious dental blanks using the portable expert diagnostic system "Lira-100"; and prevention of the phenomenon of galvanic pathology in the oral cavity, as well as the study of compensatory-adaptive changes in the oral cavity. For this purpose, 103 patients (53 women and 50 men from 39 to 63 years old) wearing metal prostheses of various designs were examined. Among them, there were 59 patients with metal prostheses cast from granules and 44 patients with metal prostheses made from rods, who were previously diagnosed with oral galvanosis and who lived in unfavorable environmental zones